Pembentukan Karakter Kristiani Siswa di SD Kecamatan Madidir Kota Bitung - Sicilia Sambur; Ester Heydemans; Meily Wagiu (Peneliti.net, 2022)
The purpose of this study, namely to obtain the results of analysis and description of data about strategies for forming students' Christian character at SDN Inpres 12/79 Wangurer and SDN Inpres 6/75 Madidir, the factors that hinder the formation of Christian character in students at SDN Inpres 12/79 Wangurer and SDN Inpres 6/75 Madidir, then efforts to improve the Christian Character Formation of Students at SDN Inpres 12/79 Wangurer and SDN Inpres 6/75. To achieve the research objectives, the researchers used qualitative research methods using a multi-case study strategy in data collection, namely, observation, interviews and document studies, then the data obtained were analyzed through analytical procedures with several stages, namely data collection, data reduction, data presentation, and drawing conclusions /verification Based on the results of the study, the researchers concluded that (1) character building strategies are still lacking, teachers are not yet fully an example and role model in the formation of students' Christian character (2) inhibiting factors are due to parents who do not support and collaborate with schools (3) efforts are being made to assist students in particular and hold a meeting with parents then give a simple explanation of God's word that Jesus is one example that should be followed (4) the strategy of character building in coaching is in a subtle way, there is also a firm way, a comfortable learning atmosphere, home visits then there is worship together (5) an inhibiting factor because of a hard heart to be reprimanded and embraced because of the habits of parents at home who do not pay attention to students and rarely go to school (6) the efforts made are cooperation between teachers and parents because without the role of parents in shaping the character of students it will be in vain then create a comfortable and understandable learning atmosphere